2007
DOI: 10.1002/jrs.1823
|View full text |Cite
|
Sign up to set email alerts
|

Raman and infrared investigations at room temperature of the internal modes behaviour in solid nitromethane‐h3 and ‐d3 up to 45 GPa

Abstract: International audienceRaman and infrared spectra of internal phonons in solid nitromethane-h3 and -d3 were measured as a function of pressure in the range 0 – 40 GPa at room temperature. Experiments were performed in diamond anvil cells. The evolution of the splitting of the various modes in condition of nearly hydrostatic compression supports the maintenance of the P21 21 21 crystal structure until the material chemically transforms into an amorphous phase. The observed pressure-induced shifts of vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
3
12
1
Order By: Relevance
“…III, it is found that the mentioned modes are from CH 3 and NO 2 stretching modes at ambient conditions and hydrostatic compression shows significant effect on CH 3 and NO 2 groups. A similar behavior has been observed from 9 to 13 GPa in the experiments using Raman measurements [8][9][10] . The variation under pressure of lattice modes are shown in Fig.…”
Section: Vibrational Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…III, it is found that the mentioned modes are from CH 3 and NO 2 stretching modes at ambient conditions and hydrostatic compression shows significant effect on CH 3 and NO 2 groups. A similar behavior has been observed from 9 to 13 GPa in the experiments using Raman measurements [8][9][10] . The variation under pressure of lattice modes are shown in Fig.…”
Section: Vibrational Propertiessupporting
confidence: 85%
“…It is insensitive, safe to handle, used as a storable monopropellant and as an additive fuel for combustion engines. Because of its simple crystal structure compared with other secondary explosives, it has been used as a prototype material to understand the energetic materials by both experimentalists [1][2][3][4][5][6][7][8][9][10] and theoreticians. [11][12][13][14][15][16][17] Nitromethane is liquid at room temperature but the molecules condense to form a solid at around 4.2 K. Trivero et al 1 first reported X-rays and neutron diffraction experiments, and found that solid nitromethane crystalizes in an orthorhombic structure in the space group P2 1 2 1 2 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Given that Phase IV has two molecules in the primitive unit cell [4], Davydov splitting is an obvious candidate to explain the splitting in the ν 3 mode commencing immediately upon crystallization and shown both here and in Shimizu et al [3]. Because the Davydov splitting is due to the interaction between the two molecules comprising the unit cell, it is to be expected that the magnitude of the splitting increases with density increase as observed here and also in other systems [18].…”
Section: Discussionsupporting
confidence: 54%
“…High-pressure Raman spectra of an L-methionine (C 5 H 11 NO 2 S) crystal for pressures up to 5 GPa were obtained by Lima et al [234] The results show strong modifications of band intensities induced by the applied pressure particularly affecting CO 2 − related bands. Room temperature Raman and infrared investigations of the behaviour of internal modes in solid nitromethane-h 3 and -d 3 up to 45 GPa were performed by Ouillon et al [235] It was concluded that the main part of the observed vibrational changes originates from the weak molecular distortion that occurs during the compression process, without any modification of the crystal symmetry. A highpressure Raman study of alane polymorphs (α-and γ -forms of AlH 3 ) by Tkacz et al [236] revealed a change in the slope of the Raman shift-pressure dependence at a pressure of 8-9 GPa for α-AlH 3 , due to a monoclinic distortion of the initially hexagonal α-AlH 3 , whereas a complete change of the Raman spectrum was observed at pressures of 11-12 GPa for γ -AlH 3 , which points to a structural phase transition from the γ -to the α-phase of AlH 3 .…”
Section: High-pressure Studiesmentioning
confidence: 99%